TANDA-TANDA VERBAL DAN VISUAL DARI PESERTA INTERAKTIF DALAM POSTER FILM SPIDER-MAN - Shella Puspita Dewi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
Advertisements contain a variety of visual and verbal signs that have their own meaning. The study aims to investigate more about Multimodal Discourse Analysis related to Spider-Man movie posters. To this end, researchers conducted a review of the relation of visual and verbal signs with interactive participants (audiences) with nine (9) posters from the superhero movie "Spider-Man" which are taken from the Internet Movie Database (IMDb). Method of qualitative descriptive analysis are written in accordance with the Royce Intersemiotic Framework (2001). The findings show that in the "Spider-Man" movie poster there is a relationship which includes visual signs (visual contact, social distance, participation, power relation and modality) and verbal signs (mood and residue) to interactive participants. The conclusion that can be produced is that most of the posters with visual techniques and declarative modalities become a connector between images to the audiences. Such visual and verbal characterizations show that dramatic representations in posters easily touch the emotions of the audience. Eventually lead to the influence of actions on the audiences and imagining the character and storyline of the movies and attracts the audiences to watch it.